Coexistence of Type I Diabetes and Lupus Nephritis in a Young Child - Rohit Badge; Vinay Rathore; Amritava Ghosh; Anish Kumar Saha; Naman Pathak (Indian Journal of Kidney Diseases)
Systemic lupus erythematosus (SLE) and type I diabetes (T1D) are autoimmune diseases that rarely occur together in the same patient. Both SLE and T1D are frequent causes of end-stage renal diseases if not treated adequately. The rate of progression of chronic kidney disease will be higher if T1D and SLE coexist in the same patient. We present a case of a 13-year-old female child with T1D and SLE. Only a few case reports of coexisting T1D and SLE are mentioned in the literature. Our case probably is one such rare case in a child with both T1D and SLE.